Ceruminous Adenoma : A Case Report and Review of Literature - Boon, Wei Jie; Yee, Leong Wa; Kin, Foong Seong; Tang, Ing Ping; Nur Shazwaniza, Awang Basry; Kevin Ng, Boon Han (Springer Nature, 2024)
Ceruminous adenoma is a rare and benign tumor of the external auditory canal and present with a nonspecific symptom. Biopsy with histopathology examination is required to establish the diagnosis. Wide local excision of tumour shows favourable outcome with a low recurrence rate. Here, we present a case of ceruminous adenoma masquerading as a furunculosis